2009
DOI: 10.4037/ccn2009249
|View full text |Cite|
|
Sign up to set email alerts
|

Edgar Allan Poe, “The Pit and the Pendulum,” and Ventricular Assist Devices

Abstract: I was sick-sick unto death with that long agony; and when they at length unbound me, and I was permitted to sit, I felt that my senses were leaving me. The sentence-the dread sentence of death-was the last distinct accentuation which reached my ears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…[23][24][25][26][27][28] Common causes of fear and anxiety included device-related issues (eg, malfunction, durability, infection, and stroke) 23,25 and uncertainty of the future. 28 In view of the remarkable advancements in mechanical circulatory support technology (eg, smaller and quieter pumps), fear and anxiety remain as the most common distressing symptoms reported by patients since the first documented out-of-hospital use of LVADs 2 decades ago. 18 Yet other studies have reported patients coping and accepting the situation of living with an implantable LVAD.…”
Section: Early Adjustment Stagementioning
confidence: 99%
“…[23][24][25][26][27][28] Common causes of fear and anxiety included device-related issues (eg, malfunction, durability, infection, and stroke) 23,25 and uncertainty of the future. 28 In view of the remarkable advancements in mechanical circulatory support technology (eg, smaller and quieter pumps), fear and anxiety remain as the most common distressing symptoms reported by patients since the first documented out-of-hospital use of LVADs 2 decades ago. 18 Yet other studies have reported patients coping and accepting the situation of living with an implantable LVAD.…”
Section: Early Adjustment Stagementioning
confidence: 99%
“…5 It has been suggested that the realities of living with the device may not be fully appreciated until they are personally experienced. 6 The VAD can be a source of fear and anxiety, 7,8 it can lead recipients to experience a loss of independence, [7][8][9][10] and distress about the uncertainty of their situation. 11 In the USA and Canada there are over 15,000 people living with VADs.…”
Section: Introductionmentioning
confidence: 99%
“…The studies show that life on MCS required major adjustment for both patients and their caregivers, and that the early experience could be frightening and overwhelming. [28][29][30] Despite a new lease on life offered by the treatment, MCS affected multiple aspects of life, including hygiene, sleep, the environment, daily routines, and personal and intimate relationships. 28,31 An initial adjustment period of ≈3 months was difficult for both MCS recipients and informal caregivers.…”
Section: Expectations For Daily Lifementioning
confidence: 99%